Análise da dor, capacidade funcional, força e cinemática do pé em mulheres com síndrome da dor femoropatelar submetidas a dois tipos de tratamento - Lima, Bruna Maria de (2014)
Frequent pain complaints in the anterior knee, difficulties in activities of daily living, such as up and down stairs, ramps and walking are common symptoms in women with patellofemoral pain syndrome (PFPS). The syndrome is related to weakness of the lateral rotator muscles and the hip abductors, consequent changes in joint angles. The poor coaptation of the femur and patella, the various angles of the joints of the lower limb can influence the manifestation of pain. However, although we found studies on the lower limb kinematics, there is little description of the importance and influence of the foot in the syndrome. Therefore, this study aimed to evaluate the influence of two treatment programs on pain, function and three-dimensional kinematics of the legs in women with PFPS. The effects of the interventions were calculated by paired t test for parametric measurements and Friedman test with Post Hoc analysis for intra-group with non-parametric values. P values <0.05 were considered significant. Our results showed that both protocols promote significant improvement of the power levels of the abductor muscles and lateral rotators of the hip and knee extensors. Strength training was effective for both patients FG as for SMG. There was a statistically significant increase in torque of the abductor muscles (P = 0, 011; P = 0.039 respectively) and lateral rotator (P = 0.025; P = 0.005 respectively) of the hip and knee extension (P = 0.002; P = 0.005 respectively) . There were no differences in range of motion (ROM) intra Group Force (GF) and intra sensorimotor group (GSM), so both treatments did not influence the kinematics of the feet.